Rancang Bangun Sistem Informasi Back Office Aplikasi Telemedicine sebagai Media Pembelajaran - Anggit Widcaksono; Esi Putri Silmina (Jurnal Informatika Terpadu, 2023)
Back Office applications have a vital role in a product, including in the context of administration. This application will be used by operators or admins whom the company has trusted to monitor and generate reports on the performance of a product or service. It should be emphasized that the Back Office application does not operate independently but has a function to monitor particular objects. This study aims to design and implement a Telemedicine-based Back Office information system application in the context of education. His background is in developing Telemedicine and the importance of efficient management in health administration. Through the type 1 prototype method approach, this research identifies user needs, builds prototypes, evaluates, and uses the system. This Back Office application is integrated with the main web-based application, enabling operators/company admins to monitor and report the performance of related products/services. The result is a system that can increase the effectiveness of education administration through information technology. This study underscores the importance of efficient Back Office management in supporting Telemedicine. Thus, this application can positively impact the delivery of education and health services through the Telemedicine approach.